Ultra-Long Range Refractive Index Fiber Sensor - Domínguez-Flores, Carmen E.; Valdés-Hernández, Alessandra I.; Reyes, Ana Karen; Monzón-Hernández, David; Rodríguez-Quiroz, Osvaldo; Ochoa-Valiente, Raúl (Frontiers in Sensors, 2022)
The dynamic range of optical fiber refractive index sensors is mainly determined by the refractive index (RI) of the sensor surface in contact with the sample under test. In the case of the refractive index sensor based on hybrid fiber Fabry-Perot interferometer (HFFPI) the largest measurable refractive index value is equal to that of the fiber core. In this work, we demonstrate that it is possible to extend the refractive index dynamic range of a HFFPI by simply adjusting the optical path length (OPL) of the air and solid cavity to be equal or differ by just a small amount. Two isometric versions of the HFFPI (i-HFFPI) with total a length of 100 and 172 µm, where the OPL of the air and solid cavity are very similar, were fabricated and tested. The interferometers were immersed in different samples with a refractive index ranging from 1.000 to 1.733. The response of the interferometers was analyzed in Fourier domain, and it was possible to establish a one-to-one relationship between the refractive index of the liquid sample and the amplitude of one of the peaks in the Fourier spectra. The amplitude of this peak experienced a linear increment when the RI of the surrounding medium was increased. Tracking the amplitude changes of a Fourier spectrum peak is straightforward which simplifies the online monitoring of the sensor. These features make this compact refractive index fiber sensor very appealing for biosensing applications.